THE MEANINGS OF THE BALINESE 'TO EAT': A STUDY OF NATURAL SEMANTIC METALANGUAGE (NSM) - Ketut Alit Suputra, Gusti; Budirasa, Made; Dhanawaty, Ni Made; Putu Putra, A.A. (e-Journal of Linguistics, 2016)
The study discusses the meanings of 'to eat' in Balinese. It aims to describe the application of the theory of Natural Semantics Metalanguage (NSM) on the Balinese language verb, which means ' to eat'. The theory used to analyze the verb is the theory of Natural Semantics Metalanguage. The theory recognizes the principle that the natural state of a language is to maintain the form for one meaning and one meaning for one form. The study uses two types of data sources, namely: (1) primary data in the form of oral data and (2) secondary data in the form of written data related to the research topic. The method used in data collection is observation and conversation. Results of the data analysis are presented by using formal and informal methods. These results indicate that the verb “to eat” in Balinese language consists of: lexicons of ngrayunang, ngajeng, daar, nunas, nede, ngamah, nidik, nyaplok, caklok, ngleklek, dan nyanggol . Such lexicons, in addition to having the same semantic field, they also have distinctive features that differentiate one lexicon to the others.
Keywords: meta language, semantic field, and the distinctive features